Clinical impacts of sarcopenic obesity on chronic obstructive pulmonary disease: a cross-sectional study - Zilin Wang; Xiaoming Zhou; Mingming Deng; Yan Yin; Yanxia Li; Qin Zhang; Yiding Bian; Jinrui Miao; Jiaye Li; Gang Hou (BMC Pulmonary Medicine, 2023)
Abstract Background Sarcopenia and obesity are two abnormal body composition phenotypes, and sarcopenic obesity (SO) is characterized by both low skeletal muscle mass (sarcopenia) and high adiposity (obesity). SO negatively influences the clinical status of patients with chronic obstructive pulmonary disease (COPD). However, the studies exploring the prevalence and clinical effects of SO in COPD patients are limited. Our study aimed to elucidate the prevalence and impact of SO on COPD patients. Methods In this cross-sectional study, the pulmonary function, St. George’s Respiratory Questionnaire, exercise tolerance, body composition, and serum levels of resistin and TNF-α were assessed in 198 COPD patients. The clinical value of serum resistin and TNF-α for predicting SO in patients with COPD was evaluated. Results In the 198 patients with COPD, the prevalence rates of sarcopenia, obesity, and SO in COPD patients were 27.27%, 29.8%, and 9.6%, respectively. Patients with SO experienced more severe symptoms of dyspnea and worse health related quality of life. The expression of resistin increased in patients with SO compared to other patients. The AUC value of serum resistin level for predicting SO was 0.870 (95% CI: 0.799–0.940). BMI (OR: 1.474, 95% CI: 1.124–1.934) and resistin (OR: 1.001, 95% CI: 1.000-1.002) levels were independent risk factors of SO in patients with COPD in Multivariate analysis. Conclusion The prevalence rates of SO in COPD patients was 9.6%. COPD accompanied by SO is significantly associated with worse pulmonary function and poor physical performance. Serum resistin may be a potential adjunct for predicting SO in COPD patients.